2022
DOI: 10.1093/brain/awac237
|View full text |Cite
|
Sign up to set email alerts
|

Progressive multifocal leukoencephalopathy: epidemiology and spectrum of predisposing conditions

Abstract: Population-based data on the epidemiology of progressive multifocal leukoencephalopathy, its predisposing conditions and mortality rate are lacking, although such data are crucial to raise awareness among clinicians and to lay foundations for future therapeutic trials in immunomodulating therapies. In our study, patients were identified by interrogating the French national healthcare reimbursement database from January 1st, 2008 to December 31st, 2017, using progressive multifocal leukoencephalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 48 publications
1
17
1
Order By: Relevance
“…However, it is also possible that survival of "historical controls" underestimates current survival rates, as suggested by a recent nationwide study in France that found 1‐year survival following PML diagnosis of patients with hematological malignancies and primary immune deficiencies was respectively of 39.2 and 55.6%. 19 Of note, the significantly longer delay between ICI initiation and death in patients with primary immune deficiencies as compared to the other categories is an interesting observation; although the molecular heterogeneity of this subcohort precludes generalizable conclusions, further investigation into this finding may provide greater insight into mechanisms contributing to immune exhaustion and susceptibility to rescue using ICIs. The low numbers of patients in this study with underlying chronic inflammatory disease, solid neoplasm, and kidney transplantation limit interpretation in these groups.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, it is also possible that survival of "historical controls" underestimates current survival rates, as suggested by a recent nationwide study in France that found 1‐year survival following PML diagnosis of patients with hematological malignancies and primary immune deficiencies was respectively of 39.2 and 55.6%. 19 Of note, the significantly longer delay between ICI initiation and death in patients with primary immune deficiencies as compared to the other categories is an interesting observation; although the molecular heterogeneity of this subcohort precludes generalizable conclusions, further investigation into this finding may provide greater insight into mechanisms contributing to immune exhaustion and susceptibility to rescue using ICIs. The low numbers of patients in this study with underlying chronic inflammatory disease, solid neoplasm, and kidney transplantation limit interpretation in these groups.…”
Section: Discussionmentioning
confidence: 93%
“…In this study, survival of patients with hematological malignancy (50%) and primary immunodeficiency (57.1%) was greater than historically reported, suggesting a potential benefit of ICI add‐on to standard of care. However, it is also possible that survival of "historical controls" underestimates current survival rates, as suggested by a recent nationwide study in France that found 1‐year survival following PML diagnosis of patients with hematological malignancies and primary immune deficiencies was respectively of 39.2 and 55.6% 19 . Of note, the significantly longer delay between ICI initiation and death in patients with primary immune deficiencies as compared to the other categories is an interesting observation; although the molecular heterogeneity of this subcohort precludes generalizable conclusions, further investigation into this finding may provide greater insight into mechanisms contributing to immune exhaustion and susceptibility to rescue using ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…Primary JCV infection mainly occurs in childhood and is asymptomatic, after which the virus remains latent, possibly in the lymphoid organs, neuronal tissues, and/or kidneys 8 . However, in cases of cellular immune deficiency, such as HIV/AIDS, viral reactivation can result in demyelination of the central nervous system (CNS) 9 . The clinical presentation of PML varies depending on the affected cerebral areas and is nonspecific.…”
Section: Discussionmentioning
confidence: 99%
“…19 JCV transmission and the route of primary infection are not well understood; however, this most likely occurs through a fecal-oral route during childhood. 1,4,6 It has been assumed that following a period of asymptomatic viremia, JCV establishes latent and/or persistent infection in the kidney, lymphoid organs, bone marrow, and possibly the brain and elsewhere in the body. In association with immunosuppression, JCV can reactivate from sites of latency or persistency, undergoing viral genetic changes to become a pathogenic neurotropic virus.…”
Section: Pathogenesis Of Pmlmentioning
confidence: 99%
“…The mortality rate can be high, ranging from 20% to 90%, depending on the underlying condition. 1 Although no Class I evidence for JCV-specific therapy is yet available, 2 the recent encouraging application of a variety of immunotherapeutic approaches, including virus-directed T-cell therapies and checkpoint inhibitors, creates the justified hope that the development of such therapies may advance to formal testing in clinical trials. 3 This review provides a brief overview of the current understanding of PML and its clinical variants.…”
Section: Introductionmentioning
confidence: 99%